Biocontrole de nematoides com fungos - Costa, Marilene Aparecida da [UNESP] (2015)
Given the high losses that nematodes cause agriculture and the limitations and impacts of agrochemicals, as well as the continuous cultivation of host plants that provide increased populations of these pests, this study aimed to isolate, identify and fungi nematophagous evaluate the potential as biological control agents of the main species of plant-parasitic nematodes in Brazil. The fungi were isolated from soil samples collected in regions of the states of MS, MG and SP, cyst and naturally infected nematodes. To test the pathogenicity of the isolated fungal parasite eggs and cysts of Heterodera glycines by fungi Pochonia chlamydosporia, Fusarium solani and Trichoderma sp, two in vitro experiments were conducted, composed by the combination of species of nematodes with every single parasite and the witness: 1 ) parasitism capacity of Meloidogyne javanica eggs and H. glycines, and 2) parasitism capacity of H. glycines eggs within the cyst, totaling 10 and 4 treatments, respectively, and 3 repetitions each. For fungus endoparasite Catenaria sp. they were used eggs and active forms Pratylenchus brachyurus, three treatments and three replications. Eggs and infected cysts were evaluated and photomicrographed. The isolate of P. chlamydosporia stood, infested with more than 80% of the eggs of H. glycines. The fungus endoparasite Catenaria sp. parasitized 89% of active forms of P. brachyurus, and parasite eggs of the same species